Effect of skidding operations on soil carbon storage of a tropical peat swamp forest - Satrio, Anton Eko; Gandaseca, Seca; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Science Publications, 2009)
Problem statement: There is still lack of a study that compares the soil carbon storage of kuda-kuda skidding system and excavator skidding system in tropical peat swamp forests. The objective of this study was to determine whether skidding operations affects soil carbon storage of a tropical peat swamp forest. Approach: Soil sampling was conducted on two different plots (0.3 ha each plot) to a depth of 15 cm under different skidding systems at Sibu, Sarawak, Malaysia. Plots were in the same forest concession area but considerably independent from each other. The soil samples were analyzed for acidity, organic matter content, total carbon, total nitrogen and total phosphorus. The humic acid extraction was also done and soil carbon storage values were obtained by calculation. The calculation of carbon storage was by the bulk density method. Unpaired t-test was used to compare variables under the two systems and correlation analysis was used to correlate variables (pH, soil organic matter, total carbon, total nitrogen, total phosphorus, C/N ratio, C/P ratio, humic acid yield, unstable carbon and stable carbon). Results: Soil organic matter, total carbon and unstable carbon were found to be negatively correlated with nitrogen but positively correlated with C/N ratio under kuda-kuda skidding system indicating that the lower nitrogen and higher C/N ratio markedly slowed decomposition process and enabled soil organic matter to accumulate as well as total carbon. Unstable carbon stocks under excavator skidding system was found to be higher (130.200 Mg ha−1) compared with kuda-kuda skidding system (117.124 Mg ha−1), under kuda-kuda skidding system, unstable carbon stock seemed to be preserved better and this was because of the better carbon storage. Although stable carbon contents of the two systems were similar, the excavator skidding system had faster decomposition processes, thus unstable carbon stocks decomposed more and this probably affects its function as carbon storage for further periods. Total phosphorus positively correlated with nitrogen but negatively correlated with C/N ratio under kuda-kuda skidding system, indicating that low nitrogen (0.914%) results in high C/N ratio (55.236) and this may have affected phosphorus (0.024%), thus enabled organic material to accumulate instead of losses through decomposition process. The low phosphorus (0.024%) or high C/P ratio (2346.345) under kuda-kuda skidding system resulted in decreased soil pH (3.552), thus enabled soil organic matter (97.603%) and total carbon (48.802%) to accumulate as well as unstable carbon stocks (117.124 Mg ha−1). Conclusion: The application of skidding systems in this peat swamp forest possibly alters their carbon storage particularly unstable carbon by altering their decomposition rates. Kuda-kuda skidding system is able to maintain decomposition process in this peat swamp forest. Hence, unstable carbon stocks can be preserved for further persistent breakdown processes, hence maintaining their function for carbon storage.